A Fall Protection System for High-Rise Construction - Haluk Çeçen; Begüm Sertyeşilışık (Journal of Engineering)
In construction industry, the number of fatal and nonfatal occupational injuries is higher than other industries. Among causes of these accidents, “falls” play a key role. This situation reveals the importance for carrying out research in fall protection systems. In this paper, a practical, economical, and functional fall protection system is introduced. Following determination and evaluation of existing solutions, weekly brainstorming meetings were held among the responsible project staff (general coordinator, project coordinator, project manager, site manager, and health and safety manager). As a result of these meetings, design criteria were developed. Based on these criteria, the fall protection system for high-rise construction (FPSFHC) was developed which satisfied all the specified design criteria. Required materials were procured from local dealers. In this paper, criteria used in design and details of the final design are presented. Field performance of the system is evaluated, and recommendations for further development and standardization of the system are added.